2020
DOI: 10.1017/s0305741019001231
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating Political Trust: The Impact of Survey Nonresponse in Rural China

Abstract: Has survey nonresponse caused scholars to overestimate political trust in China? We analyse item nonresponse for sensitive questions on trust in government from our original survey of villagers conducted in China in 2012. We also analyse nonresponse in four other comparable surveys conducted in China between 1993 and 2014. We examine the association between nonresponse to politically sensitive questions and individual characteristics such as sex, level of education, Party membership and cosmopolitanism. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Consistent with similar studies conducted in this region (Nash et al, 2016;, our sample was biased toward men and people with lower levels of education, possibly because men can have a higher willingness to interact with strangers in rural China, and might be more likely to agree to be interviewed compared to women (Ratigan and Rabin, 2020). The villages we surveyed represent some of the poorest and underdeveloped communities in Hainan (and indeed across China), which is why overall education levels are low amongst interviewees (Davies and Wismer, 2007;Gu and Wall, 2007), and people who attain higher education from such communities in China tend to migrate to urban areas to seek better employment opportunities (Gu and Wall, 2007).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent with similar studies conducted in this region (Nash et al, 2016;, our sample was biased toward men and people with lower levels of education, possibly because men can have a higher willingness to interact with strangers in rural China, and might be more likely to agree to be interviewed compared to women (Ratigan and Rabin, 2020). The villages we surveyed represent some of the poorest and underdeveloped communities in Hainan (and indeed across China), which is why overall education levels are low amongst interviewees (Davies and Wismer, 2007;Gu and Wall, 2007), and people who attain higher education from such communities in China tend to migrate to urban areas to seek better employment opportunities (Gu and Wall, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…Researchers' positions as independent from government authorities were clearly explained to interviewees, emphasizing that they were students wanting to learn about the local environment. Researchers were not accompanied by local officials because this has been known to affect responses (Davies and Wismer, 2007;Ratigan and Rabin, 2020). Standard Mandarin was used in all interviews, which the interviewees could understand.…”
Section: Data Collectionmentioning
confidence: 99%
“…This incident left us to rethink the ethical and methodological issues of conducting Internet user research in an informational autarchy. Nonresponse is still a common issue concerning politically sensitive surveys in China (Ratigan & Rabin, 2020). Nonresponses may complicate inference from survey research, where bias arises from demographic factors like education and political background; for instance, 18% of respondents in our study chose not to report their partisan affiliations.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for self-censorship in Chinese public opinion surveys is mixed; while several studies have found evidence for self-censorship in measures of political support, others cast doubt on the prevalence of political wariness. Some studies have found that Chinese respondents are likely to overstate their support for the government (Robinson and Tannenberg, 2019; Shen and Truex, 2020), and their trust in the central government (Ratigan and Rabin, 2020). Others argue that political sensitivity is unlikely to be severe enough to inflate measures of trust.…”
Section: Discussionmentioning
confidence: 99%